Crocodylocapillaria longiovata n. gen., n. sp. (Nematoda: Capillariidae) from the stomach of crocodiles in Australia and New Guinea - Moravec, F; Spratt, D M (The Journal of parasitology, 1998)
A new nematode, Crocodylocapillaria longiovata n. gen. and n. sp., is described from the stomach of wild and farmed young crocodiles, Crocodylus johnstoni Krefft, and Crocodylus porosus Schneider, from northern Australia and Papua New Guinea; it is undoubtedly identical with the nematodes previously reported as Capillaria sp. from Crocodylus novaequineae Schmidt from Irian Jaya, Indonesia. This capillariid species represents a new genus, being characterized mainly by the presence of elongate eggs with unusually long protruding polar plugs, a well developed vulvar appendage, a weakly sclerotized spicule, proximal and distal parts of the spicular sheath with spines, and the male posterior end with 2 large lateral caudal lobes and a pair of papillae near the cloacal opening. The body length of C. longiovara males and females is 5,576-7,208 microm and 8,609-14,008 microm, respectively, the spicule is 276-369 microm long; the size of the egg proper is 48-60 x 15-21 microm, length of polar plugs 15-18 microm. Neocapillaria Yi and Guitang, 1994, a junior homonym of Neocapillaria Moravec, 1987, is re-named Sinocapillaria nom. n. and placed as a synonym of Pseudocapillaria Freitas, 1959. Indocapillaria De and Maity, 1995 is retained as a subgenus of Pseudocapillaria because of the possession of a vulvar appendage in the type species. Neocapillaria Moravec, 1987 remains a subgenus of Capillaria Zeder, 1800. A key to genera of the Capillariidae from poikilotherm vertebrates is provided; C. longiovata is the first capillariid species described from the digestive tract of crocodiles.
Keywords: Severní teritorium; infekce hlísticemi řádu Enoplida; Stomach; Female; Northern Territory; Papua New Guinea; Alligators and Crocodiles; Animals; Enoplida Infections; ženské pohlaví; mužské pohlaví; Male; Trichinelloidea; zvířata; žaludek; Papua Nová Guinea; Trichuroidea; aligátoři a krokodýli